2018
DOI: 10.1139/cjes-2016-0120
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical, geological, and hydrogeological characterization of a tributary buried bedrock valley in southern Ontario

Abstract: Buried bedrock valleys infilled with Quaternary-aged sediment have the potential to become productive aquifers owing to prevalent sand and gravel deposits often associated with these topographic lows. In areas where groundwater is drawn from the underlying bedrock aquifer, buried bedrock channels may significantly affect the spatial distribution of recharge and localized contaminant pathways. Therefore, understanding the form, distribution, and the nature of Quaternary infill sediments within these buried bedr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…9). The basal gravel in core GDC-1A likely formed by in situ weathering of the underlying bedrock or is colluvium deposited along the steep walls of the bedrock valley (Steelman et al 2017). Stratigraphically, this rubble may be preglacial, associated with pre-Catfish Creek ice or may be associated with the overlying diamict (Table 1).…”
Section: Geological Conceptual Model Of the Paris Morainementioning
confidence: 99%
“…9). The basal gravel in core GDC-1A likely formed by in situ weathering of the underlying bedrock or is colluvium deposited along the steep walls of the bedrock valley (Steelman et al 2017). Stratigraphically, this rubble may be preglacial, associated with pre-Catfish Creek ice or may be associated with the overlying diamict (Table 1).…”
Section: Geological Conceptual Model Of the Paris Morainementioning
confidence: 99%
“…1; black hatched lines represent the location of the cross sections in Fig. 4 (Karrow 1968(Karrow , 1987Gao et al 2006;Cole et al 2009) and observed in recently drilled boreholes within the study area (Steelman et al 2018). Relief on the bedrock topography surface is important in both local and regional groundwater applications, as it has an impact on the distribution of recharge to underlying bedrock aquifers.…”
Section: Comparing the Nature And Geometry Of Stratigraphic Unitsmentioning
confidence: 90%
“…5), which is also consistent with previous findings based on standard geological cross sections through the area (Blackport et al 2009;McGill 2012;Arnaud et al 2018), where subsurface heterogeneity, lateral discontinuity of geologic units, and (or) the relief on the underlying bedrock surface lead to rapid changes in unit thicknesses. For example, the basal diamict that underlies the outwash plain is not always preserved (McGill 2012), and the regional Catfish Creek Till thickens considerably from <5 m to over 25 m as it infills a topographic low in the underlying bedrock surface (Steelman et al 2018). …”
Section: Comparing the Nature And Geometry Of Stratigraphic Unitsmentioning
confidence: 99%
“…The first paper on buried valleys in this issue, by Steelman et al (2018), provides a geophysical investigation of a gorge-style valley in the city of Guelph. An evaluation of the effectiveness of electrical resistivity and seismic refraction methods is supported with borehole and hydraulic information; this was used to map the spatial distribution of sediments and the delineation of a valley segment of a regional bedrock valley.…”
Section: Buried Valleysmentioning
confidence: 99%
“…More recently, using the regional bedrock topographic model (Gao et al 2006), three classes of buried valleys have been identified by Russell et al (2007) on the basis of valley length, width, and position in the landscape, which from smallest to largest are (i) gorges, (ii) escarpment re-entrants, and (iii) escarpment troughs. An additional class of buried valleys is sediment-hosted tunnel valleys, most extensively developed in the Greater Toronto Area (e.g., Brennand et al 2006).The first paper on buried valleys in this issue, by Steelman et al (2018), provides a geophysical investigation of a gorge-style valley in the city of Guelph. An evaluation of the effectiveness of electrical resistivity and seismic refraction methods is supported with borehole and hydraulic information; this was used to map the spatial distribution of sediments and the delineation of a valley segment of a regional bedrock valley.…”
mentioning
confidence: 99%